Changes in lipid profile of corpus luteum throughout the estrous cycle in buffalo - Sharma, R K; Neeru, Neeru; Chauhan, M S (The Indian Journal of Animal Sciences, 2012)
A biochemical study has been made on qualitative changes in lipids of corpora lutea during the estrous cycle in buffalo. The total lipid content increased up to day 11 (30.17±3.52 mg/g) and then decreased. The phospholipids (4.64±2.43 µg/100 mg) and cholesterol content (5.65±1.45 µg/100 mg) as well as phospolipids/cholestrol ratio (0.82) were minimum in day 13 to 17 Corpora lutea. Regressing corpora lutea depicted maximum glycolipid (14.97µg/mg) and free fatty acid (0.61 µg/100 mg) content. Triglycerides were maximum in the day 1 to day 15 corpora lutea (84.9±0.45µg/100 mg). All these lipid changes shall be discussed in relation to the metabolic status of corpora lutea vis-a-vis hormonal titre and ultrastructural changes.